Degree of satisfaction in the assistance training of the resident of general surgery of the public university - Salazar-Reyna, María Dolores (2020)
Objective. To determine the degree of satisfaction in the care training of the resident doctors of general surgery of the National University of San Marcos. Methods. Observational, cross-sectional, descriptive study. A satisfaction survey was applied to 80 general surgery resident physicians from the Universidad Nacional Mayor de San Marcos in 2015. Results. The average age was 31 years, the age range was 26 to 42 years, 77% were male and 23% were female. 79% were satisfied with the number of patients seen in the emergency room. 66% were satisfied with the number of preoperative preparations. 68% were satisfied with the number of postoperative care. Conclusions. Resident general surgery physicians at the Universidad Nacional Mayor de San Marcos are satisfied whit their academic care training.